Left Ventricular Diastolic Dysfunction in Liver Cirrhotic Patients: Proportion, Correlation, and Relationship of Diastolic Parameters with Stage of Liver Dysfunction - Prionggo Mondrowinduro; Irsan Hasan; Idrus Alwi; Murdani Abdullah (Jurnal Penyakit Dalam Indonesia)
Introduction. Cardiovascular complication of liver cirrhosis is relatively obscure. Pathophysiology of liver cirrhosis, involving portal hypertension made the possibility of cirrhosis complication manifested as left ventricular diastolic dysfunction. This study aims to determine proportion of left ventricular diastolic dysfunction among liver cirrhotic patients according to American Society of Echocardiography-European Association of Echocardiography (ASE-EAE) 2009 and conventional approach, to determine any correlation between left ventricular diastolic dysfunction severity stages with severity stages of liver dysfunction in cirrhotic patients represented by Child Turcotte Pugh (CTP ) score, also to asses relationship between severity stages of parameters of diastolic function according to ASE-EAE 2009 with liver cirrhosis severity evaluated by numerical CTP score.